E-at, curated mindful eating experience - Jiang, Nan (Nanyang Technological University, 2021)
E-at (eat-at) is a curated dining experience to highlight the importance of mindful eating. As captured in the title, to be aware of the present moment experience with food. The set-up aims to initiate inner dialogues with food, and the counterpart sharing the table. Through interacting with the reflective element, figuratively, one could reflect on what to eat and how to eat. A set of complementary tableware was designed to facilitate the process of mindful eating by rationing food portions and bringing variety to the table. Mindful eating aims to reconcile unhealthy relationships with food. This project stemmed from the needs of the community suffering from eating disorders. Uncontrolled eating habits played a major contributing role to the development of chronic diseases and other mental illnesses. Since increased emphasis has been placed on healthy eating on a global scale, mindful eating practices could provide valuable solution to eating disorders.